'PrEP'ing Memphis: A qualitative process evaluation of peer navigation support. (February 2022) - Pichon, Latrice C.; Teti, Michelle; Betts, Joshua E.; Brantley, Meredith
Highlights: Accessing clients at testing events increases interest level in PrEP navigation. Accompanying clients to first appointments facilitate PrEP uptake. Rapport building with patient and clinic staff enhance PrEP navigation strategies. Abstract: Background: HIV PrEP (pre-exposure prophylaxis) navigation comprises intervention strategies used to improve PrEP uptake via education, linkage, and follow-up/ongoing engagement. During 2016–2019, the Tennessee Department of Health (TDH) implemented a CDC-funded demonstration project ("Project PrIDE") focused on PrEP navigation in Memphis community-based organizations (CBOs) and the Shelby County Health Department (HD). A process evaluation was conducted to determine facilitators and barriers to the implementation of the Memphis-based Project PrIDE PrEP navigation activities. Methods: A total of fourteen in-depth qualitative interviews were conducted, with nine PrEP navigators in evaluation year 1 (2018) and five of the original navigators in evaluation year 2 (2019), to understand the navigation processes using thematic analysis. Results: Facilitators of PrEP navigation included accessing clients at testing events, accompanying clients to first appointments, rapport building with patient and clinic staff, and maintaining consistent engagement with clients. Factors impeding PrEP navigation included difficulties assessing client readiness, tracking client navigation status, and stigmatizing clinic and social experiences for clients. Conclusions and lessons learned: Findings have informed the scale-up of PrEP navigation implementation statewide, along with priority setting and resource allocation for the local Ending the HIV Epidemic (EHE) initiative in Memphis.